Penerapan Model Pembelajaran Probing Prompting pada Pembelajaran IPA di SMP 3 Selong - Kholida Ismatulloh; Ropikoh Ropikoh (Kappa Journal, 2021)
The study, entitled "Application of the Probing Prompting Learning Model in Science Lessons at SMPN 3 Selong" aims to determine the influence of students in understanding the concept of learning science in the classroom. The research subjects were students of class VIII at SMPN 3 Selong, namely class VIII D and class VIII E, with the data retrieval process using a written test of 6 items of description. The average value obtained in the control class is 63.48 while the experimental class is 80.48 with a difference of 17 points. For the hypothesis value thitung = 2.042 while ttabel = 1.079 from the results of the calculation of the hypothesis test results of learning science students obtained thitung> ttabel =, then the hypothesis alternative (Ha) is accepted. So it can be concluded that there is an influence in the application of the probing prompting learning model in science learning at SMP 3 Selong